2008
DOI: 10.1155/2008/810961
|View full text |Cite
|
Sign up to set email alerts
|

Soft Drink Consumption Linked with Fatty Liver in the Absence of Traditional Risk Factors

Abstract: BACKGROUND: Little is known about dietary habits and their relationships with liver disease in nonalcoholic fatty liver disease (NAFLD) patients, particularly in the absence of obesity, diabetes or hyperlipidemia. OBJECTIVE: To assess the association between soft drink consumption and the presence of fatty liver in NAFLD patients who do not have classic risk factors. METHODS: Three hundred ten patients with NAFLD diagnosed by ultrasound were assessed for 36 months in a cross-sectional manner. Thirty-one patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
194
0
11

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(219 citation statements)
references
References 34 publications
(42 reference statements)
11
194
0
11
Order By: Relevance
“…Recently, it has been shown that a diet low in fructose might be beneficial with regard to reduction of liver fat content. 21,22 However, the exact mechanisms involved in sugar and particularly fructose-induced NAFLD are still poorly understood. Here, by feeding mice lacking the endotoxin receptor TLR-4 chronically with a moderate fructose-enhanced diet (e.g., 30% fructose in drinking solutions) we further tested the hypothesis that the endotoxin-induced activation of hepatic Kupffer cells resulting from intestinal bacterial overgrowth and increased intestinal permeability 13,14 is a key factor in the onset of fructose-induced NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that a diet low in fructose might be beneficial with regard to reduction of liver fat content. 21,22 However, the exact mechanisms involved in sugar and particularly fructose-induced NAFLD are still poorly understood. Here, by feeding mice lacking the endotoxin receptor TLR-4 chronically with a moderate fructose-enhanced diet (e.g., 30% fructose in drinking solutions) we further tested the hypothesis that the endotoxin-induced activation of hepatic Kupffer cells resulting from intestinal bacterial overgrowth and increased intestinal permeability 13,14 is a key factor in the onset of fructose-induced NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Fructose and high-fructose corn syrup, a common soft drink sweetener, in particular, have been independently connected to the risk and severity of NAFLD in population-based studies and in a randomised crossover trial [115][116][117][118][119].…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…Results of several recent studies suggest that an increased intake of dietary fructose may be associated with the development of NAFLD. 23,25 Further, the CARDIA study has shown that fast-food consumption had a strong positive association with weight gain and insulin resistance in humans. 26 However, aerated drinks or fast-food consumption did not show any association with NAFLD in our study.…”
Section: Singh Et Al Risk Factors Associated With Non-alcoholic Fattymentioning
confidence: 99%